The Effect Of Part And Whole Learning Model On Increasing Self Confidence In Learning Backward Roll Floor Gymnastics Of Students Of Class VII SMPN 4 Karawang Barat - Resa Ristiana; Muhammad Mury Syafei; Citra Resita (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to determine the effect of the Part and Whole learning model on improving students' self-confidence in floor exercise learning, specifically in the backward roll technique. The main issue addressed is the low self-confidence of students, particularly female students, in performing floor exercise movements, which hinders the effectiveness of physical education learning. This research uses a quantitative approach with a quasi-experimental method and a one-group pretest-posttest design. The participant consisted of 40 students from class VII C of SMP Negeri 4 Karawang Barat, selected using purposive sampling. The research instrument was a self-confidence questionnaire covering four main dimensions: self-belief, perseverance, hope, and social relationships. The results showed an increase in the average self-confidence score from 128.70 in the pretest to 136.90 in the posttest. Data analysis using the paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest results. Thus, it can be concluded that the Part and Whole learning model has a positive and significant effect on increasing students' self-confidence in learning the backward roll in floor gymnastics.